Republic of Korea : 2022 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for the Republic of Korea. (IMF Staff Country Reports; Country Report, 2022)
Korea has recovered impressively from the COVID-19 pandemic, which is a testament to its strong economic fundamentals and the authorities' able policy responses. Activity has surpassed pre-covid levels despite multiple COVID waves. The recovery was supported by the effective containment of the pandemic, including rapid vaccination in 2021, and pursuing proactive economic policy support, which helped minimize economic scarring, sustain income growth, and maintain financial stability. Given Korea's high global integration, strong external demand also supported the recovery. The upcoming presidential election offers a window of opportunity to reinvigorate structural reforms.